Metode Penentuan Awal Bulan Empat Mazhab - Muhammad Faishol Amin (Universitas Negeri Jakarta, 2018)
There is a problem of determining the beginning of the lunar month among Muslims. They split into different group of opinions and maintain their distinct interpretations as ijtihad against the others. This problem started from the different interpretations of the hadith. Some of them understand it textually that produces ru’yah faction, and some prefer a contextual understanding then belong to the hisab faction. Furthermore, it study underlines the need to understand about how the previous ‘ulama (salaf) argued, especially the ‘ulama of four madhhabs, whose their argument often used as a reference by the ‘ulama of today (khalaf). In this discussion it found that the opinions of the ‘ulama of four madhhab are different. Some used ru’yah and some other used hisab. This is natural as it is the product of ijtihad that each mujtahid has various interpretations. Thus, Muslims have two options: between the scientific determination (Shari’ah/Astronomy) or corporative determination (Unification Calendar). These two options are very difficult to compromise, and one of them must be selected.